Regioselective deuteration of alcohols in D2O catalysed by homogeneous manganese and iron pincer complexes. Issue 12 (4th June 2018) - Kar, Sayan; Goeppert, Alain; Sen, Raktim; Kothandaraman, Jotheeswari; Surya Prakash, G. K.
Abstract : Regioselective, base-metal catalyzed deuteration of alcohols in D2 O. Abstract : We report a convenient and cost-effective protocol for the regioselective deuteration of primary and secondary alcohols using Earth abundant homogeneous first row transition metal pincer catalysts. D2 O is utilized as both a deuterium source and a solvent, allowing for a benign inexpensive process. Depending on the metal selected (Mn or Fe), a high degree of deuterium incorporation was observed selectively either at the α and β position (Mn) or exclusively at the α position (Fe), for primary alcohols. This simple, efficient, and cost-effective protocol for alcohol C–H bond deuteration constitutes a powerful tool for the large scale synthesis of deuterated molecules.